Efektivitas Uji Kelayakan Pembiayaan di BQ Bina Insan Mandiri - Muhammad Maulana (Media Syari'ah, 2012)
Baitul Qiradh Bina Insan Mandiri has a commitment to fund the people whose focus on microfinance so that they have more opportunity to develop their business by increasing the capital. Although BQ Bina Insan faces high risk of level, BQ tries to overcome the problem professionally by using decent standard test even there are many obstacles because micro-entrepreneurs are not able to fulfill the main standard. The examined aspects include market and marketing aspect, production technique and technology aspect, management and human resources, low and legality aspect as well as finance and economic aspect. Baitul Qiradh Bina Insan Mandiri is very flexible in applying its feasibility concept by considering the effort of microfinance customers and its limited coverage aspects.